Establishment of a trial period in agency contracts: comments in the context of the judgment of the Court of Justice (Ius Novum, 2020)
Commercial agency contracts are of great economic importance and have a long tradition of normative regulation. Minimum standards of protection common to the EU member states are laid down in the Directive 86/653/EEC on self-employed commercial agents. The constant changes in the legal environment mean something more than just ‘interpretation of a norm’, the need to reach for its well-established, uniform, common understanding expressed in the case law and judicial decisions. The importance in this respect must unquestionably be attached to the preliminary rulings of the Court of Justice. An interesting point in its case law is the recent reference to the question of whether agency contracts concluded for a trial period are bound by the provisions of that act. Although this is the first time when the Court of Justice has addressed this issue, the direction of the interpretation, presented in favour of resolving the national court’s doubts, is more broadly based on the desire to extend the protective mechanisms of the Directive to commercial agents that are bound by contracts which do not fully comply with the classic agency format. Based on the analyses carried out in the paper, it can be concluded that the trend to deformalise the law is correct and should be the subject of broader legal discourse.
Keywords: commercial agent; agency contract; trial period contract; teleological interpretation; indemnity